The bank lending channel in Turkey: Has it changed after the low inflation regime? - A. Nazif Catik; Mehmet Karaçuka (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
In this paper we aim to analyze the role of credit channel in the monetary transmission mechanism under different inflationary environments in Turkey covering the period 1986:1 - 2009:10. Our results suggest that traditional interest rate channel is only valid for the postinflation targeting period. This variable is also more effective monetary policy tool in terms of its impacts on economic activity in the both regimes. Credit shocks itself have significant power on economic activity and prices. However, the effect of monetary shocks on credit volume is very limited especially in the low inflation regime.
Keywords: 330